(untitled) (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2025)
Pediatric emergencies pose unique challenges to acute care relating to the physiological and developmental makeup of children. This study aims to explore the clinical profiles, systemic barriers, and solutions for pediatric emergency care in a tertiary hospital environment. A prospective observational study was conducted with 110 patients (aged 0 to 15 years) presenting to the emergency department with an acute medical or traumatic emergency and Collected data included demographic data, anthropometry, the reason for attendance, triage levels, interventions, and outcomes, Respiratory distress and trauma were the primary reasons for presentation, accounting for more than 50% of cases Though the majority of patients required supportive care, 21% were admitted to the intensive care unit furthermore The major systemic barriers identified were a lack of pediatric-specific equipment and lack of trained staff. Interventions of staff training, protocol implementation and providing adequate resources were successful measures to help overcome these barriers, where The total mortality rate was low (1%) and most of patients had resolved symptoms and were fully recovered within 30 days, These results highlight the need for pediatric-specific emergency protocols, adequate resources, and education/allowance of continuing training to improve outcomes in pediatric acute care, finally This study provided valuable insights for consideration into the improvement of pediatric emergency services in similar health service settings.